1970
DOI: 10.1002/j.2050-0416.1970.tb03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Copper in Spirits

Abstract: The principal rapid, non‐digestive methods listed in the literature were surveyed and briefly tested. The diquinolyl procedure was found to be best for copper in the 0 to 10 p.p.m. range. Below I p.p.m. the own colour of the whisky or brandy interfered with the estimation. Colour removal by active carbon altered the copper content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A number of methods have been described for the determination of copper in alcoholic liquors. In view of the low concentration of copper in these beverages, the spectrophotometric (Szobolotzky, 1970 Ogorodnik and Dranovskaya, 1976), and atomic absorption procedures (Trachman et al, 1970; AOAC, 1975) mostly were considered. Recently, an X-ray fluorescence spectrometry method (Noble et al, 1976) was also reported.…”
Section: Literature Citedmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods have been described for the determination of copper in alcoholic liquors. In view of the low concentration of copper in these beverages, the spectrophotometric (Szobolotzky, 1970 Ogorodnik and Dranovskaya, 1976), and atomic absorption procedures (Trachman et al, 1970; AOAC, 1975) mostly were considered. Recently, an X-ray fluorescence spectrometry method (Noble et al, 1976) was also reported.…”
Section: Literature Citedmentioning
confidence: 99%
“…Review of the articles show that diethyldithiocarbamate (Maneva et al, 1974), zinc dibenzyldithiocarbamate (Brandon et al, 1969), and cuprizone (Ogorodnik and Dranovskaya, 1976) are the most commonly used reagents for this purpose. Several other reagents were also employed (Szobolotzky, 1970), but most of them lack selectivity and specificity for copper analysis. 6-Phenyl-2,3-dihydro-as-triazine-3-thione (PDTT) was reported to be a specific reagent for the spectrophotometric analysis of copper (Maghssoudi and Fawzi, 1975).…”
Section: Literature Citedmentioning
confidence: 99%